Efeitos do alumínio na diferenciação neural: envolvimento da sinalização purinérgica - Reichert, Karine Paula (2020)
Aluminum (Al) is considered the most abundant metal in enviorment. In this way, all life forms are susceptible to constant exposure to this element. The trivalent cationic form of Al, Al3+, is well known for being the most toxic species for biological systems. Some studies even show that the concentration of Al3+ in the human brain may be associated with the etiology of neurodegenerative diseases, such as Alzheimer's disease (AD). However, the mechanism underlying to Al exposure and the neuropathogenesis of AD remains unclear. The purinergic system represents an important signaling pathway involved in CNS neuromodulatory mechanisms, in addition to emerging inflammatory responses through the action of specific purinoreceptors, in front of the external stimuli, such as Al. Thus, the present study evaluated the effects of Al3+ (0.1 – 100 μM) on purinergic signaling during neurogenesis of neural precursor cells (NPCs) in vitro and, in animal model of chronic exposure to Al (50 – 100 mg / kg of AlCl3). For investigate the role of Al3+ on neural development, CPNs were isolated from embryos obtained from pregnant mice. NPCs proliferate under specific conditions, in the presence of growth factors EGF and FGF-2, and form clusters of CPNs, the neurospheres. The results show that Al3+ played a decisive role in inhibiting the proliferation of NPCs during neural differentiation and, induced apoptosis in cells. Al3+ also reduced the migration of neurospheres and, consequently, the determination of the neural phenotype. Analysis by flow cytometry and immunocytochemistry showed that Al3+ promoted a decrease in the expression of the immature neuron marker β3-tubulin followed by an increase in the coexpression of Nestina and GFAP, indicating the prevalence of NPCs after exposure to Al3+. In addition, it was shown that Al3+ adheres to the cytoplasm of neurospheres, reducing the extracellular release of ATP, and decreasing the sequential hydrolysis of this nucleotide by NTPDase and 5’- nucleotidase enzymes activities, respectively. The reduction in ATP release by Al3+ was sufficient to decrease the expression of P2Y1 and A2A receptors in differentiated neurospheres. These receptors are crucial for the proliferation and self-renewal of NPCs during brain development. On the other hand, in the model of chronic oral exposure (30 days) to Al3+ in Swiss mice, in the form of AlCl3, the metal was able to reduced brain weight and accumulated in the hippocampus of animals treated with 100 mg / kg of salt. Memory deficits and DNA damage induced by Al3+ were observed. The hydrolysis of ATP was also affected by the treatment with the metal, indicating an increase in the NTPDase, 5'-nucleotidase and ADA enzymes activities. In addition, Al3+ increased the density of P2X7 and A2A receptors, as well as the proinflammatory cytokine IL-1β. Taken together, the data obtained in this study show that Al3+ causes cell damage and inhibits the differentiation of NPCs, possibly due to changes in purinergic signaling. In addition, chronic exposure to metal in vivo caused mnemonic damage and neuroinflammation associated with the purinergic pathway.